Balancing Secrecy and Transparency in Bug Bounty Programs. - Telang, Rahul; Hydari, Muhammad Zia (Communications of the ACM, 2025)
Bug bounty programs (BBPs) allow ethical hackers to identify software vulnerabilities, helping vendors fix flaws before they’re exploited—but vendors often control disclosure, creating a lack of transparency. This secrecy can delay patches, obscure software quality, and leave users uninformed about security risks. While BBPs offer clear benefits, such as reducing uncoordinated disclosures and incentivizing ethical behavior, they also reinforce market asymmetries. The article argues for mandatory disclosure standards and stronger government oversight to balance transparency with vendor incentives, ultimately strengthening cybersecurity and user trust.